2011
DOI: 10.2174/1874357901105010124
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Differences Unfold a Wide Range of Enterotoxigenic Abilities Exhibited by rNSP4 Peptides from Different Rotavirus Strains

Abstract: NSP4 has been recognized as the rotavirus-encoded enterotoxin. However, a few studies failed to support its diarrheagenic activity. As recombinant NSP4 (rNSP4) peptides of different lengths were used in the limited number of studies, a comparison of relative diarrheagenic potential of NSP4 from different strains could not be possible. To better understand the diarrheagenic potential of NSP4 from different strains, in this report we have evaluated the enterotoxigenic activity of the deletion mutant ΔN72 that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Also, in a study, NSP4 peptides (residue 120-147) has shown disordered type of CD spectra in buffer and undergo significant conformational transitions in membranous environment [117]. The aforementioned disordered regions of NSP4 play a key role in the initiation of diarrhea and binding to DLP [112,113]. The MoRF region (residues 124-131) resides in the region that is responsible for many functions such as residue 112-148 utilized as the VP4 binding domain residues 112-140 for Caveolin binding, and residues 112-135 used for Ca +2 binding and enterotoxin domain {Table 2 and Fig.…”
Section: Non-structural Protein Nsp4mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in a study, NSP4 peptides (residue 120-147) has shown disordered type of CD spectra in buffer and undergo significant conformational transitions in membranous environment [117]. The aforementioned disordered regions of NSP4 play a key role in the initiation of diarrhea and binding to DLP [112,113]. The MoRF region (residues 124-131) resides in the region that is responsible for many functions such as residue 112-148 utilized as the VP4 binding domain residues 112-140 for Caveolin binding, and residues 112-135 used for Ca +2 binding and enterotoxin domain {Table 2 and Fig.…”
Section: Non-structural Protein Nsp4mentioning
confidence: 99%
“…It is the first identified viral enterotoxin [110,111]. The flexible C-terminal cytoplasmic region (residues 161-175) of NSP4 binds to VP6 of the DLPs and mediates their entry into the ER lumen where the virus becomes temporarily enveloped [112,113] and matures into TLP. NSP4 interacts with microtubules and immobilizes the early secretory pathway [114,115].…”
Section: Non-structural Protein Nsp4mentioning
confidence: 99%
“…NSP4 is the only RV-encoded protein that triggers the release of Ca 2ϩ from the ER (18)(19)(20) by functioning as a viroporin in infected cells (21). NSP4 also is an oligomeric protein that can adopt multiple forms, which depend on the fragment of NSP4 being analyzed and whether NSP4 is expressed with other RV proteins (22)(23)(24)(25). Predictions indicate NSP4 has multiple putative Ca 2ϩ -binding sites (26); however, available structural information provides evidence only for a Ca 2ϩ -binding site positioned in the core of the tetrameric coiled-coil structure formed by the NSP4 CCD, which folds into an ␣-helical conformation.…”
Section: The Nonstructural Protein Nsp4 Of Rotavirus Is a Multifunctimentioning
confidence: 99%